Tinjauan Teologis Prinsip-prinsip Penggembalaan dalam Yeremia 23: 1-4 - Setya Budi Tamtomo (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2020)
Many pastors have become stumbling blocks due to their inability to dedicate their lives to God's calling, in applying pastoral principles. Through a descriptive qualitative method with a literature study approach, the author describes the theological review of the shepherding principle being the main goal of exegesis in Jeremiah 23: 1-4. So that the pastor's role can be maximized by understanding and actualizing the principles of shepherding. The principle of shepherding in Jeremiah 23: 1-4 found that shepherding is the ministry of finding the lost and scattered congregations, gathering the scattered congregations and bringing them back to worship and giving courage not to be afraid to face the problems at hand. Pastors are also required to care about the condition of their congregation both physically and spiritually. The pastor must care for, find and gather the congregation back.